Finite-alphabet based channel estimation for OFDM and related multicarrier systems. - Shengli Zhou (IEEE Transactions on communications)
Novel blind channel estimators based on the finite alphabet property of information symbols are derived in this paper for OFDM and related multicarrier code-division multiple access (MC-CDMA) systems. The resulting algorithms are applicable not only to standard OFDM transmitters with cyclic prefix, but also to the zero padded OFDM transmissions that improve symbol recovery at the expense of altering the transmitter and complicating the equalizer. Based on FFT-processed received data, channel identifiability is guaranteed regardless of channel zero locations and various channel estimation algorithms become available by trading on the complexity for performance. Unlike existing blind channel estimators, the proposed alternatives require short data records especially for PSK transmissions. The inherent scalar ambiguity is easily resolved because it has unit amplitude and phase values drawn from a finite set. Decoupling channel from symbol estimation enables a phase-directed operation that improves upon decision-directed schemes that are known to suffer from error propagation. Practical issues are also addressed including the presence of frequency guard intervals, constellation and power loading, various frame designs, coded transmissions as well as semi-blind and online implementations for systems with training sequences. The algorithms are tested with simulations and also compared with existing alternatives in a realistic HIPERLAN/2 setting